2015
DOI: 10.1007/s12264-014-1519-z
|View full text |Cite
|
Sign up to set email alerts
|

Zinc binds to and directly inhibits protein phosphatase 2A in vitro

Abstract: Zinc induces protein phosphatase 2A (PP2A) inactivation and tau hyperphosphorylation through PP2A (tyrosine 307) phosphorylation in cells and the brain, but whether Zn 2+ has a direct inhibitory effect on PP2A is not clear. Here we explored the effect of Zn 2+ on PP2A and their direct interaction in vitro. The results showed that Zn 2+ mimicked the inhibitory effect of okadaic acid on protein phosphatase and prevented tau dephosphorylation in N2a cell lysates. PP2A activity assays indicated that a low concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Cations such as zinc and iron are found in the senile plaques in AD brains with high concentrations [74][75][76] . We have reported that zinc inhibits PP2A directly through binding to PP2Ac (51-270) in vitro [77] . Zinc can also induce PP2A phosphorylation at tyrosine 307 (Y307) and lead to tau hyperphosphorylation [78] .…”
Section: Metal Chelatorsmentioning
confidence: 98%
“…Cations such as zinc and iron are found in the senile plaques in AD brains with high concentrations [74][75][76] . We have reported that zinc inhibits PP2A directly through binding to PP2Ac (51-270) in vitro [77] . Zinc can also induce PP2A phosphorylation at tyrosine 307 (Y307) and lead to tau hyperphosphorylation [78] .…”
Section: Metal Chelatorsmentioning
confidence: 98%
“…By dephosphorylating these key signaling molecules, a number of phosphatases have been shown to “put the brakes” on IFN signaling. Phosphatases tyrosine-protein phosphatase non-receptor type 6 (SHP1), type 11 (SHP2), and protein phosphatase 2A (PP2A) have all been shown to inhibit JAK-STAT phosphorylation ( 153–155 ), and are all inhibited by zinc ions, predominantly in the nanomolar range ( 156–158 ). Interestingly, PP2A can also inhibit the phosphorylation of IRF3, thus regulating antigen recognition by PRRs ( 159 ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Another study has agreeably demonstrated zinc-induced aggregation of Aβ peptides in vitro [ 36 ]. Recently, zinc has also been demonstrated to induce tau hyperphosphorylation by activating the glycogen synthase kinase-3beta (GSK-3β) and inactivating phosphatase like protein phosphatase 2A (PP2A) [ 18 , 35 , 37 ]. However, whether zinc-mediated tau hyperphosphorylation involves the GSK-3β kinase remains controversial as some studies show that the GSK-3β kinase is not activated and only PP2A is inactivated under zinc-induced tau hyperphosphorylation conditions [ 38 ].…”
Section: Essential Biometal Ionsmentioning
confidence: 99%